The Role of Amphiregulin in Exemestane-Resistant Breast Cancer Cells: Evidence of an Autocrine Loop - Wang, Xin (2008)
Exemestane-resistant breast cancer cell lines (i.e., ExeR), derived from MCF-7 cells expressing a high level of aromatase (MCF-7aro), were generated in our laboratory. The epidermal growth factor (EGF)—like protein amphiregulin (AREG) was highly expressed in ExeR cells based on cDNA microarray analysis. The high levels of AREG mRNA in ExeR cell lines were confirmed by real-time reverse transcription-PCR. The high levels of AREG protein in ExeR cell lysates and culture media were confirmed by Western blot analysis and ELISA, respectively. Furthermore, our Western blot analysis showed that whereas no AREG was detected in the DMSO control, overnight treatment of parental MCF-7aro cells with 1 μmol/L exemestane strongly induced the expression of AREG. This induction was totally blocked by 100 nmol/L of pure antiestrogen ICI 182,780, implying estrogen receptor (ER) dependence of exemestane-induced AREG expression. MCF-7aro cells were not able to proliferate in hormone-free medium, but were able to proliferate in conditioned medium from ExeR cells, similar to the treatment of recombinant human AREG. Small interference RNA targeting AREG inhibited ExeR proliferation, confirming that AREG is truly functioning as a growth factor of ExeR cells. The specific inhibitors to ER (ICI 182,780), EGF receptor (EGFR; AG1478), and mitogen-activated protein kinase (MAPK; U0126) all showed dose-dependent suppression of the proliferation of ExeR cells, indicating the involvement of the ER, EGFR, and MAPK pathways. Based on these findings, we propose a possible mechanism that underlies exemestane resistance: exemestane induces AREG in an ER-dependent manner. AREG then activates the EGFR pathway and leads to the activation of the MAPK pathway that drives cell proliferation.